Tewa Worlds : An Archaeological History of Being and Becoming in the Pueblo Southwest - Duwe, Samuel (Book collections on Project MUSE., 2020)
"Tewa Worlds offers an archaeological history of eight centuries of Tewa Pueblo history in the Rio Chama Valley through the lens of contemporary Pueblo philosophical and historical discourse. The result gives weight to the deep past, colonial encounters, and modern experiences. It challenges archaeologists to both critically reframe interpretation and to acknowledge the Tewa's deep but ongoing connection with the land"--